Qualidade da madeira de árvores de clone de Eucalyptus grandis x Eucalyptus urophylla inclinadas por ação de ventos para produção de celulose - Boschetti, Walter Torezani Neto (2014)
This study aimed to evaluate the wood quality of trees inclined of clone Eucalyptus grandis x Eucalyptus urophylla from forest plantations affected by the action of winds for pulp production. For this purpose, was evaluated the effects of inclination, and studied the characteristics of the reaction wood, tension wood and opposite wood, the upper wood and the lower inclination, respectively. The productivity was evaluated by the parameters dendrometric trees. The quality of the wood was analyzed by means of anatomical parameters of fiber and vessels, basic density and chemical composition. The kraft pulping performance was analyzed based on screened yield and kappa number. The dendrometric parameters, anatomical parameters, the basic density and chemical composition of wood were influenced by the inclination of the trunk. The results showed that negatively affect the tilt dendrometric variables, reducing the amount of timber; the heart:sapwood ratio of trees was not affected; there was a greater eccentricity of the pith in trees with greater inclination stem. Anatomically, the vascular diameter was larger compared with normal wood in the reaction wood, tension and opposite; vascular frequency was little affected by the inclination ranges; the fibers of wood reaction by the tree inclined, tension and opposite wood, increased wall thickness, width and lumen diameter. The density of the wood of inclined trees was less to wood from trees with the straight stem, furthermore, the inclined trees, basic density was lower in the opposite wood compared to tension wood. The chemical composition was different between straight trees and leaning trees, the reaction wood, tension and opposite, content of lower extractives and lignin than normal wood, another important factor is the higher holocellulose content found in the reaction wood was found. In kraft pulp was observed the reaction wood lower yield pulp and lower kappa number. Finally, considering the technological properties of wood and kraft evaluation, realized that the basic density and wood anatomy reaction of leaning trees helped reduce the x screened yield pulp, and chemical composition of wood of leaning trees contributed to obtain pulps with higher content of delignification.